Differential treatment in the provision of medication abortion at pharmacies in Uttar Pradesh, IndiaAJOG Global Reports at a Glance - Joanna Percher, MPH; Malvika Saxena, MPH; Aradhana Srivastava, PhD; Nadia Diamond-Smith, PhD (Elsevier, 2021)
BACKGROUND: Almost 3 quarters of India's roughly 16 million annual abortions are done through medication abortion purchased from pharmacists outside of healthcare facilities. The quality of information provided by pharmacists about medication abortion is often poor. OBJECTIVE: To determine whether pharmacists selling medication abortion provide different information or ask different, potentially stigmatizing questions to clients by gender and marital status. STUDY DESIGN: Mystery clients presenting as 4 profiles (unmarried woman, unmarried man, married woman, and married man) purchasing medication abortion interacted with 111 pharmacists in 3 districts around Lucknow, Uttar Pradesh in 2018. Data were collected immediately after the interaction. The differences in the information conveyed and the questions asked by the pharmacists by mystery client characteristics were analyzed using logistic regression in Stata 15 MP. RESULTS: Pharmacists very rarely asked intrusive, medically irrelevant questions and appeared willing to sell medication abortion to all the mystery clients regardless of gender, age, or marital status. However, the pharmacists were overall less likely to provide the female mystery clients with as comprehensive and correct information on medication abortion as they were to male mystery clients, particularly if female mystery clients presented as unmarried. CONCLUSION: Pharmacists are observed to provide differential and poorer quality information about medication abortion to women, especially if they seem unmarried, potentially putting women at risk of having a lower-quality and less supported experience of using the medication. However, the pharmacists' willingness to sell the medication to all mystery clients and the lack of intrusive questions and comments reinforces out-of-facility medication abortion as a way for individuals to access an often-stigmatized service. Interventions must find a way to either address this bias among pharmacists, or more practically, to provide high-quality information directly to the individuals seeking medication abortion.